Improving Job Satisfaction Through the Implementation of Transformational Leadership in Rsud - Garibaldi, Ganjar (Business Management, 2025)
This study aims to analyze the effect of transformational leadership implementation on employee job satisfaction at the Regional General Hospital (RSUD) in Karawang. Transformational leadership is a leadership approach that emphasizes empowerment, inspiration, intellectual stimulation, and individualized consideration toward subordinates. In the context of healthcare services, this leadership style is crucial in creating a supportive and productive work environment. The research method used is quantitative with a survey approach, involving respondents from both medical and non-medical personnel. The research instruments were developed based on indicators of transformational leadership and job satisfaction, and their validity and reliability were tested. The results of the regression analysis indicate that transformational leadership has a positive and significant effect on employee job satisfaction. This means that the higher the implementation of transformational leadership, the higher the level of job satisfaction perceived by employees. These findings have important implications for hospital management in improving employee performance and retention through a more humanistic and empowering leadership style.